Model-Informed Precision Dosing (MIPD) - Jonás Samuel Pérez-Blanco; José M. Lanao (MDPI AG, 2022)
Model-informed precision dosing (MIPD) is an advanced quantitative approach focusing on individualized dosage optimization, integrating complex mathematical and statistical models of drugs and disease combined with individual demographic and clinical patient characteristics [...]